Northern Territory electoral atlas, 1974-1984 - Jaensch, Dean, 1936-; Wade-Marshall, Deborah; Australian National University. North Australia Research Unit.; Flinders University of South Australia. Discipline of Politics (Darwin : Australian National University, North Australia Research Unit ; Adelaide : Discipline of Politics, Flinders University, 1984)
Statistical summary of the society & electoral geography of NT (1974-84); Map details areas of Aboriginal land & land under claim in 1983; results of 1981 census, including demography, occupational status & distribution, housing & mobility.
"Joint monograph North Australian Research Unit, Darwin Discipline of Politics, Flinders University".
Keywords: Northern Territory. -- Legislative Assembly -- Elections -- Maps; Northern Territory. -- Legislative Assembly -- Elections -- Statistics; Housing; Demography - Population dynamics; Land rights - Claims, disputes, hearings; Demography - Census data; Politics and Government - Elections; Demography - Population mobility; Northern Territory -- Population -- Statistics, Vital; Northern Territory (NT)